Information technologies and mathematical modelling : queueing theory and applications : 18th International Conference, ITMM 2019, named after A.F. Terpugov, Saratov, Russia, June 26-30, 2019, Revised selected papers /: queueing theory and applications : 18th International Conference, ITMM 2019, named after A.F. Terpugov, Saratov, Russia, June 26-30, 2019, Revised selected papers. (2019) - Unknown
No abstract available